Nursing interventions to promote dyspnea self-management of complex chronic patients: An integrated review - Henriques, Helga Rafael; Correia, Andreia; Santos, Tatiana; Faria, José; Sousa, Diana; Portela, Joana; Teixeira, Joana (Elsevier, 2024)
Objectives: Chronic dyspnea, a distressing symptom in patients with complex chronic conditions, is linked to higher risks of mortality. This study aimed to identify nursing interventions that could improve self-management for complex chronic patients, thereby enhancing control over chronic dyspnea. The findings intend to guide nursing care strategies that promote self-management among this population. Methods: We searched the databases Medline, Scopus, Web of Science, CINAHL, Cochrane Database of Systematic Reviews (CDSR), and Joanna Briggs Institute (JBI) databases were searched in December 2023. We included adult patients with complex chronic conditions with chronic dyspnoea. The team screened articles collaboratively, using Rayyan software. A qualitative appraisal was performed according to JBI Critical Appraisal Checklist tools. The review protocol is registered under the number CRD42023456021. Results: Our review included 18 studies that explored a variety of interventions for chronic dyspnea. We identified pharmacological interventions (such as oxygen therapy and inhalation treatments) and nonpharmacological approaches (including educational programs, breathing exercises, fluid intake management, body awareness techniques, peer support, emotional intelligence training, and the use of web applications). Those interventions empower patients, improve their ability to fulfill life roles, mitigate emotional distress, and improve overall quality of life. Nursing care can be crucial in enabling individuals to achieve independence and autonomy in self-care. Conclusions: Promoting self-management for chronic dyspnea in complex chronic patients requires a holistic approach, encompassing multidisciplinary interventions, individualized self-care education, peer engagement, and technological support. Current research on self-management inadequately addresses interventions targeting patient behaviour change. It highlights the need to delve deeper into the selfmanagement process. Further research is needed to expand the evidence base and refine these interventions.
Keywords: Chronic disease; Dyspnea; Nursing; Patient; Self-management